Effect of transformation texture on the impact toughness of hot-rolled Ti + Nb microalloyed steel - Sasidhar K.N.; Dhande T.; Javed N.; Ghosh A.; Mukherjee M.; Sharma V.; Mahashabde V.V.; Das Bakshi S. (My University, 2025)
The impact toughnesses of a Ti + Nb HSLA steel plate, conventionally hot rolled in the austenitic region, were measured at four different directions at 0 °C, −20 °C and −40 °C respectively. The microstructure was characterised using light optical microscope, scanning electron microscope (SEM) followed by evaluation of hot rolled texture from the Orientation Distribution Function (ODF) obtained from the electron back-scattered diffraction (EBSD) data. The anisotropy in the yield strength (YS) and impact toughness was then correlated with the microstructural features and key texture components. The microstructure was comprised of polygonal ferrite + cementite (< 5 vol%) with a planar distribution of cementite in the RD-TD plane in the form of structural banding due to solute segregation. The transformation texture developed at the mid-section of the RD-TD plane was found to be comprised of the (a) RD-fiber (i.e. ⟨110⟩∥ RD), (b) the ND-fiber (i.e. ⟨111⟩∥ ND) and (c) the rotated-cube components in the ⟨100⟩∥ ND-fiber. The marginal anisotropy observed in YS is attributed to the formation of RD-fiber (⟨110⟩∥ RD), specially high intensity of the {112}⟨110⟩ component of the fiber. In impact toughness, the delamination followed by ductile tearing observed at 0 °C, is attributed to the planar banding of cementite in RD-TD plane with minimal impact of crystallographic texture. At −40 °C, the observed anisotropy in impact toughness properties and cleavage mode of fracture, are attributed to the (a) high volume fraction of grains oriented in the {001} and {110} planes and (b) rotated-cube {001}⟨110⟩ and two components of ND-fiber, namely, {111}⟨112⟩ and {111}⟨110⟩. © 2017 Elsevier Ltd